Effects of Paddy Straw Incorporation on Growth and Yield Attributes of Low Land Rice - Swain, Jevelin; Paikaray, Rabindra Kumar; Nayak, Rabindra Kumar; Panda, Rajendra Kumar (Bangladesh Journal of Botany, 2022)
A field experiment on effects of paddy straw incorporation on growth, physiology and yield attributes of low land rice was conducted at Agronomy experimental field of Central farm, College of Agriculture, Bhubaneswar during rabi-2020.The experiment was laid out in completely randomized block design with six treatments symbolyzed as T1 to T6 along with recommended dose of fertiliser (80:40:40::N: P2O5:K2O kg/ha). Results showed highest plant height, tiller number, leaf number, SPAD and LCC were in T5 followed by T4 and T6. These parameters were found to be highly correlated with grain yield. The growth analysis during different period of growth of the rice cultivar, Lalat, in respect to leaf area index(LAI), crop growth rate(CGR), specific leaf area(SLA), leaf area ratio(LAR), LAD(leaf area duration), total chlorophyll, total carbohydrate, amino acid and protein contents were found to be correlated with grain yield. Maximum values regarding these parameters were found to be highest in T5 followed by T4 and T6. The total biomass was found significant among the treatments and was highest in T5 followed by T4 and T6. Grain yield and straw yield were found to be highly correlated with total biomass (r2=0.70) and physiological growth traits (LAI, SLA, CGR) were prominently significant in T5 with a tune of 4.94t/ha and 5.21t/ha, respectively followed by T4 and T6. In T5 yield attributing parameters like number of panicles, panicle weight, filled grain per panicle, 1000-grain weight were highest. The high percentage of C, H, N, S concentration and high ratio of C:N, C:H implies good quality grain harvested in T5. The soil microbial population and status after harvest was also found to be high inT5. Thus, paddy straw incorporation coupled with chemical fertilizer had significant effect on rice growth and yield with proper maintenance of microbial population in soil when the crop is treated with T5 with booster application of 20 kg/ha of N and P in the form of urea and DAP, respectively. Bangladesh J. Bot. 51(4): 713-719, 2022 (December)